Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Motivasi dan Hasil Belajar Mahasiswa Pendidikan Biologi STKIP Pembangunan Indonesia Makassar - Astuti, Wiwik Wiji; Nurveryani, Andi (Biology Teaching and Learning, 2018)
Abstract.  This research is a quasi-experimental research that aims to determine the Differences in Student Learning Outcomes of Biology Education STKIP Indonesian Development based on Gender Differences through the       Thisresearch is a quasi-experimental research that aims to determine the positive effect of Think Pair Share (TPS) Cooperative Learning Models on the Motivation and Learning Outcomes of Biology Education Students STKIP Indonesia Makassar Development. The subjects of this study were students of VIE class as experimental class and VID class as control class with 25 students each. The instruments used in this study were motivation questionnaires and student biology learning outcomes tests. Data were obtained through two instruments, namely learning motivation questionnaire and learning outcome test. Data analysis was performed using descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis of the motivation value of the control class average value is on a scale of 4.08 with good category and the experimental class the average value is on a scale of 4.30 with a very good category. The results of descriptive analysis of the value of the learning outcomes of the control class an average value of 70.56 and the experimental class the average value of 79.04. The results of hypothesis testing are obtained by Sig. (2-tailed) = 0.001 <α = 0.05, H0 is rejected and H1 is accepted. This shows that there is a positive influence on the application of Cooperative Learning Model Type Think Pair Share (TPS) to the learning outcomes of biological education students in STKIP Pembangunan Indonesia Makassar. Keywords: TPS cooperative learning model, motivation, and learning outcomes.